1943
DOI: 10.1113/jphysiol.1943.sp004029
|View full text |Cite
|
Sign up to set email alerts
|

The influence of posture on the pulmonary blood volume and the alveolar gas tensions

Abstract: In a recent series of papers Main has dealt with the problem of the fall in the tension of the carbon dioxide in the alveolar air which occurs on the assumption of the erect postur,e. In 1937 he suggested that it was due to an increase in pulmonaiy ventilation. Hitchcock & Ferguson [1938] disagreed with this and pointed out that the phenomenon took place without an increase in ventilation of the lungs. In two of the latter's subjects there was both a fall in the pulmonary ventilation and in the alveolar C02 te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1953
1953
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Such a spontaneous rhythm might be responsible for some of the changes ascribed to sleep. Others may be ascribable to posture, since recumbency (Mackay, 1943) leads to a rise in alveolar C02 tension.…”
mentioning
confidence: 99%
“…Such a spontaneous rhythm might be responsible for some of the changes ascribed to sleep. Others may be ascribable to posture, since recumbency (Mackay, 1943) leads to a rise in alveolar C02 tension.…”
mentioning
confidence: 99%
“…Further, any emotional disturbances would be expected to lessen with repetition of the test, out in fact the expiratory shift did not change with repeated suit inflation. The symptomatic response was remarkably slight even when the suit was inflated with the subjects in the head-down position; there was no evidence of the " marked sense of suffocation " described by MacKay [1943] following the release of tourniquets around the lower limbs. A change of pulmonary compliance would also affect expiratory reserve.…”
Section: Associated Changes In Pulmonary Compliancementioning
confidence: 92%
“…If the hyperventilation with oxygen can be explained in terms of a local accumulation of carbon dioxide in the tissues of the respiratory centre, as has been suggested by Lambertsen et al (1953), a fall in alveolar carbon dioxide concentration would be expected. MacKay (1943) has suggested that a change in pulmonary flow can also alter alveolar carbon dioxide concentration independently of changes in ventilation. There is some evidence that oxygen brings about a small reduction in cardiac output (Whitehorn, Edelmann & Hitchcock, 1946;Dripps & Comroe, 1947), but it seems unlikely that relative over-ventilation persists for more than the immediate period of adjustment in pulmonary flow.…”
Section: Resultsmentioning
confidence: 99%